THE EFFECT OF LIGHTNING ON HIGH VOLTAGE ELECTRICAL SUBSTATIONS’ LOW VOLTAGE SYSTEMS - M. I. Fursanov; P. V. Kriksin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2016)
The article presents the results of studies of the effects of lightning on low voltage systems of high voltage electrical substations with outdoor switchgears of 110 kV. The topicality of research is associated with a wide spreading of such substations as well as with a high reliability requirements of their work and, also, with their widespread distribution and high probability of lightning strikes to the substation or around it. The highest probable and the most dangerous effects of lightning on low voltage systems of a substation are determined on the basis of critical review and special literature analysis and, also, of systematization of practical information that had been collected during the survey of operating substations. Adequate physical models were developed for the list of hazardous effects based on physical processes of lightning. A model of each effect was studied on the basis of the sensitivity theory. The accuracy and adequacy of the models were verified by means of comparison of calculation results for the models under investigation with the results of calculations fulfilled in accordance with specialized programs, as well as from practical or theoretical data obtained by other authors. The factors that had been included in the models were studied and were defined in accordance with their nature (natural or artificial), the range of possible values in a substation was determined; the coefficients of elasticity were calculated. The obtained results enable to ascertain the contribution of the factor in the effect of lightning and the ability to control the factor. The relationship between the factors and the effects of lightning are shown as graphs. For practical application the information, obtained as the result of the research, was organized in the form of checklists that can be applied when collecting baseline information to develop the lightning protection of the substation, to examine the existing lightning protection, to investigate emergency situations associated with lightning strikes. The results of the study were used in practice during the pre-design survey of substations, development of the design assignment, design of lightning protection of a substation, and during fulfillment of acceptance tests and periodic inspections of lightning protection.